INTEGRATING ISLAMIC VALUES IN PROJECT-BASED LEARNING TO ENHANCE STUDENT CREATIVITY THROUGH MARKET DAY - Saiful Bahri; Hayaturrohman Hayaturrohman; Ade Nurpriatna (PEDAGOGIK : JURNAL PENDIDIKAN, 2025)
This study examines the limited integration of values-based education and 21st-century competencies into learning practices. This is particularly relevant to enhancing students' creativity and self-directed learning through authentic activities. The purpose of this study was to examine how Market Day activities implement Project-Based Learning (PjBL), how Islamic values are incorporated into them, and how these activities foster student creativity and self-directed learning. The study employed a qualitative case study method, with participants being purposively selected based on their participation in the learning process. An interactive model used condensation, display, and inference to analyze data from various sources. Triangulation techniques were also used to ensure data validity. The results indicate that Market Day-based PjBL is structured through structured planning, implementation, and evaluation stages. Islamic values such as honesty, responsibility, cooperation, and fairness are also embedded in students' social and transactional activities. Furthermore, the learning process allows students to engage in reflective activities, task organization, and idea generation; this indicates increased creativity and self-directed learning. The results indicate that Market Day-based PjBL serves as an integrative learning model that connects experiential learning with value internalization. This helps build broader competencies in education.